Kemenarikan Desa Wisata Budaya Liang Ndara di Manggarai Barat Nusa Tenggara Timur - Hiasinta Hiani; Enok Maryani; Taufik Hidayat (Tourism Scientific Journal, 2022)
Liang Ndara is a tourism village that is developed based on culture. The distance from Komodo National Park is about 20 km with a travel time of only 45 minutes. The number of tourist visits continues to increase, but the increase is much faster to Komodo National Park than to Liang Ndara Village. The purpose of this study was to find out the attractions in Liang Ndara Tourism Village and what obstacles faced by tourists visiting Komodo National Park to come to Liang Ndara Tourism Village. The research was conducted using a survey method with a questionnaire as a data collection tool. The number of respondents was 250 people, and the data was obtained qualitatively with percentages as a means of interpretation. The results showed that Liang Ndara Village has natural, cultural and historical attractions, but accessibility, amenities, and tourism activities are still limited. The main obstacle for tourists not to visit Liang Ndara village is ignorance and travel agents do not introduce or market Liang Ndara Village. Therefore, marketing and promotion need to be carried out in an integrated manner, and the government can be the spearhead to socialize Liang Ndara Village both directly to the tourist market and to travel agents.